Filtrate from the culture medium of the mushroom Pycnoporus sanguineus in the control of Alternaria sp. - Pereira, Leonel Bismarck Belo; de Jesus, Michele Santos; Correia, David Patrick Almeida; Villwock, Ana Paula Schervinski; Viégas, Pedro Roberto Almeida; Marino, Regina Helena [UNESP] (Centro Universitario de Maringa, 2024)
The use of microorganisms in the control of phytopathogens is an ecological alternative to synthetic pesticides, as they do not cause environmental contamination. The study evaluted the antifungal activity of Pycnoporus sanguinues (PS) on the mycelial growth of the phytopathogenic fungus Alternaria sp. (ALT), in two bioassays. In the first bioassay, a completely randomized experimental design was used in the factorial scheme of 4 x 5, corresponding to the cultivation of fungal isolates in four treatments: PS - PS witness; ALT - ALT witness; ALT x PS - interaction of the ALT with PS; and PS x ALT - interaction of the PS with ALT, during five days of evaluation (2nd to 6th day of cultivation) with four replications per treatment. In the second bioassay, a completely randomized experimental design was used in the factorial scheme of 4 x 4 corresponding to four treatments: Test-15: witness with 15% of the culture medium used to obtain the fungal filtrate, without fungal inoculation; Test-30: witness with 30% of the culture medium used to obtain fungal filtrate, without fungal inoculation; PS-15: 15% filtered from PS culture medium; and PS-30: 30% of filtrate from the PS culture medium during four days of evaluation (2nd to 5th day of cultivation) with three replications per treatment. Pycnoporus sanguineus inhibits mycelial growth of the phytopathogenic fungus Alternaria sp., depending on the time of cultivation. The use of 15% and 30% of the filtrate of the culture medium of P. sanguineus inhibits the mycelial growth of Alternaria sp.
Filtrado do meio de cultivo do cogumelo Pycnoporus sanguineus no controle de Alternaria sp.
Keywords: Basidiomycete; Biological control; White rot fungus